Examining Islamic Environmental, Social and Governance (ESG) Current and Future Research– A Bibliometric Analysis - Ahmad Saiful Azlin Puteh Salin; Suryani Abdul Raman; Nik Nurul Aswani Nik Kamarudin; Siti Nabilah Mohd Shaari (Information Management and Business Review, 2024)
This bibliometric analysis offers a comprehensive look at the current research trends in Islamic environmental, social, and governance (ESG) over 12 years, from 2012 to 2023. The study encompasses a dataset of 54 papers from the SCOPUS database and employs various bibliometric metrics, including author-based, country-based, and organization-based citations. The results indicate a variable growth in the number of publications in this research domain over the period, with a particularly significant surge observed between 2021 and 2023. The descriptive analysis identifies the most prolific countries and document types within Islamic environmental, social, and governance realms. The citation analysis identifies the most influential authors, organizations, and countries shaping this field. In summary, the results show that environmental, social, and governance (ESG) research and practices that include Islamic teachings and values still demonstrate a significant gap, and recommendations are provided for future research based on the primary issues and gaps discovered from the current trends. These findings are valuable for researchers, practitioners, and policymakers seeking insights into this study area.